Expediency of usung the worked out agent of the drying - Gaponjuk, Igor; Bulyandra, Alexey (My University, 2012)
Dvuhshahtnye dryer type DSP- 32 is the most common in Ukraine. The actual energy in the drying of grain dryers twice calculated need for phase transformation in the grain moisture . The greatest heat loss occurs with Used working gases. The feasibility of using the heat of these gases must be compared with the cost of technical support proposals recovery . The least expensive , but less environmentally - safe sentences can 0.5 pay within the dryer season . Eco-friendly deals with use of heat pipes can be paid back within 5 years.
Keywords: сушка; drying; зерно; grain; енергоємність; энергоемкость; energy; сушарка; сушилка; dryer; рекуперація тепла; рекуперация тепла; heat recovery; кафедра теплоенергетики та холодильної техніки; кафедра технології зберігання і переробки зерна